2019
DOI: 10.17756/nwj.2019-072
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Silar Cycle on The Energy Bandgap of Iron Copper Sulphide (FeCuS) Thin Films Deposited on SLG Substrate

Abstract: This study aims to investigate the influence of SILAR cycle on the energy bandgap of Iron Copper Sulphide (FeCuS) thin films deposited on soda-lime glass substrate (SLG). A Successive Ionic Layer Adsorption and Reaction (SILAR) method is one of the chemical methods for making uniform and large area thin films, which is based on immersion of substrates into separately placed cationic and anionic precursors. The technological importance of chemically deposited iron copper sulphide (FeCuS) using SILAR technique v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…For samples deposited at 60 and 70 SILAR cycles, band gap values increased with the cycle, whereas the sample deposited at 50 SILAR cycles had a higher band gap value of 2.99 eV. There is an obvious contrast between the range of these direct energy band gap values and the result of Adeniji et al, 2020. The values obtained were found to be lower which could be attributed to the variation of SILAR cycle used.…”
Section: Uv-visible Studiesmentioning
confidence: 86%
See 1 more Smart Citation
“…For samples deposited at 60 and 70 SILAR cycles, band gap values increased with the cycle, whereas the sample deposited at 50 SILAR cycles had a higher band gap value of 2.99 eV. There is an obvious contrast between the range of these direct energy band gap values and the result of Adeniji et al, 2020. The values obtained were found to be lower which could be attributed to the variation of SILAR cycle used.…”
Section: Uv-visible Studiesmentioning
confidence: 86%
“…The production of these thin films is done in this modification by submerging the substrate in cationic and anionic precursors that are placed independently, and then cleaning the substrate with ion-exchanged water in between each immersion in order to prevent homogenous precipitation in the solution. Several researchers have successfully deposited FeCuS thin films by the use of chemical bath deposition (CBD) (Obasi et al, 2016), solution growth technique (SGT) (Uhuegbu, 2010) and SILAR technique (Adeniji et al, 2020). In this work, we use the SILAR technique to deposit FeCuS thin films by the use of Triethanolamine acid (TEA) and Ethylenediaminetetraacetic acid (EDTA) as complexing agents.…”
Section: Introductionmentioning
confidence: 99%
“…Similar sheet resistivity measurements for ZnS were obtained using Van der Pauw technique in the order of 10 2 Ω-cm to 10 1 Ω-cm and electrical conductivity of 10 -3 to 10 -2 (Ω-cm) -1 by Shinde et al (2011). Adeniji et al 2020 reported that when conductivity increases as the heat treatment increases, it enhances the electrical properties of ZTS thin films and this made the ZTS a good candidate for solar cell fabrication.…”
Section: Electrical Propertiesmentioning
confidence: 99%